2018
DOI: 10.1039/c8sc02470g
|View full text |Cite
|
Sign up to set email alerts
|

Replacing H+by Na+or K+in phosphopeptide anions and cations prevents electron capture dissociation

Abstract: By successively replacing H+ by Na+ or K+ in phosphopeptide anions and cations, we show that the efficiency of fragmentation into c and z˙ or c˙ and z fragments from N–Cα backbone bond cleavage by negative ion electron capture dissociation (niECD) and electron capture dissociation (ECD) substantially decreases with increasing number of alkali ions attached.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 118 publications
(153 reference statements)
1
12
0
Order By: Relevance
“…FT-ICR mass spectrometry. All experiments were performed on a 7 T FT-ICR instrument (Apex Ultra, Bruker, Austria) equipped with an ESI source, a linear quadrupole for ion isolation, a collision cell for CAD 59 (Argon gas flow through the collision cell was 0.2 l s −1 ), and an indirectly heated hollow cathode for electron capture dissociation (ECD) 57 . Electrostatic potentials and radiofrequency voltages of ion transfer elements (funnel, hexapole, quadrupole, and ion lenses) were optimized for maximum ion transmission, and the skimmer potential 58 adjusted for efficient ion desolvation and dissociation of piperidine adducts (40 V for RRE-TR-0 and RRE-IIB-0, and 60 V for RRE-II-0).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FT-ICR mass spectrometry. All experiments were performed on a 7 T FT-ICR instrument (Apex Ultra, Bruker, Austria) equipped with an ESI source, a linear quadrupole for ion isolation, a collision cell for CAD 59 (Argon gas flow through the collision cell was 0.2 l s −1 ), and an indirectly heated hollow cathode for electron capture dissociation (ECD) 57 . Electrostatic potentials and radiofrequency voltages of ion transfer elements (funnel, hexapole, quadrupole, and ion lenses) were optimized for maximum ion transmission, and the skimmer potential 58 adjusted for efficient ion desolvation and dissociation of piperidine adducts (40 V for RRE-TR-0 and RRE-IIB-0, and 60 V for RRE-II-0).…”
Section: Discussionmentioning
confidence: 99%
“…Peptides were desalted by diluting ~200 µl rev peptide solution in H 2 O (~1 mM) with 1.8–3.8 ml aqueous ammonium acetate (100 mM) solution, followed by concentration to 200–500 µl using centrifugal concentrators (Microsep Advance, MWCO 1000, Pall Corporation, USA, or Vivaspin 2, MWCO 2000, Sartorius AG, Germany); the concentration-dilution process was repeated 4–5 times and followed by 5–6 cycles of concentration and dilution with H 2 O. The rev ARM peptide sequence was confirmed by electron capture dissociation (ECD) MS 57 . H 2 O was purified to 18 MΩ cm at room temperature using a Milli-Q system (Millipore, Austria), CH 3 OH (Acros, Austria) was HPLC-grade, ammonium acetate (≥99.0%) and piperidine (≥99.5%) were from Sigma-Aldrich (Austria).…”
Section: Methodsmentioning
confidence: 99%
“…2,3,5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] The position of the radical in the peptide and its ability to migrate along the peptide backbone or to the amino acid side chains in the open-shell fragment ions have been explored in a large number of experimental and theoretical investigations. The so-called Cornell 2,11,17,53 and Utah-Washington 8,10,12,[18][19][20][21]35,[54][55][56] mechanisms are the best-known hypotheses describing ExD dissociation reactions. In the Cornell mechanism, electron attachment occurs at a protonated site in the ion that is hydrogen-bonded to a nearby carbonyl, whereas according to the Utah-Washington mechanism, the electron is directly captured in a p* orbital of an amide carbonyl group, stabilized by H-bonding to a protonated site.…”
mentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18] A lot of gaseous RNA-peptide interactions have been demonstrated in past years which showed that noncovalent interactions can be stronger than covalent interactions. 12,[18][19][20][21] A recent study by Kathrin Breuker et al demonstrated that the interactions between transactivation response element (TAR) RNA and a peptide are strongly electrostatic (gas phase) to survive RNA backbone bond cleavage by collisionally activated dissociation (CAD), thus permitting binding sites in TAR RNA. 12 Interestingly the concept behind these experiments depend on the relative strength of covalent and noncovalent interactions: If the covalent bonds are more stable, the composition and stoichiometry of complex is analyzed, whereas if the noncovalent interactions are more stable, it is easy to determine the initial structures, binding sites, and the thermodynamic information of small gaseous complexes with higher accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…12 The unusual strength of TARÀtat interactions in the gas phase was attributed to electrostatic interactions and it was anticipated that the salt bridges have provided the highest contribution to stability. 19,31 These approaches gave highly accurate thermodynamic information for noncovalent interactions in small gaseous complexes 23 but it is difficult to obtain data with high accuracy for larger systems in which the strength of individual neutral (10-40 kJ/mol) 32 and ionic (20-170 kJ/mol) hydrogen bonds (HBs) is modulated by other charges and noncovalent bonds. In the same way, the stability of salt bridges between protonated basic (arginine side chains) and deprotonated acidic (RNA phosphodiester moieties) sites is strongly affected by the number and distribution of other charges and hydrogen-bonding sites.…”
Section: Introductionmentioning
confidence: 99%